FUTURE TRENDS ON THE SPOT IN INTERNATIONAL TOURISM - MODERN YOUTH EDUCATIONAL TOURISM - Diana Foris; Cristina Nicolau; Tiberiu Foris (European Scientific Journal, ESJ, 2014)
This paper is focused on the future trends in international tourism, being of outmost importance to underline that international tourism is emerging while developing new forms of tourism, as for example, youth educational tourism. Hence, there will find success those regions, resorts, businesses that rely themselves on the flexibility and creativity of their services provided, whereas using all the natural resources in an environmentally friendly way. Furthermore, this research shows that as an emerging form of tourism, youth educational tourism shall be re-designed so as to meet the needs of its beneficiaries, being a challenge for tourism providers who shall consider it as a great opportunity to start and develop new businesses and to undertake the challenges offered by the tourists' new visions in the hospitality industry. In this view, the marketing research on the consumers' needs had as general objective to identify the tendency on the Romanian market by analysing the youth's attitudes and behaviours towards educational camps.